Current Trends in Tonometry and Tonometer Tip Disinfection. Issue 7 (July 2020) - Junk, Anna K.; Chang, Ta Chen; Vanner, Elizabeth; Chen, Teresa
Abstract : Precis: A survey among members of the American Glaucoma Society (AGS) and the American Optometry Association (AOA) on tonometer preference and tonometer disinfection indicates a shift to disposable tonometer tips compared with 1987. Purpose: This survey's purpose was to determine how eye care providers responded to the 2008 Centers of Disease Control (CDC) tonometer disinfection guidelines, which recommend 10% hypochlorite (dilute bleach) for reusable tonometers. Tonometers measure the eye pressure when they touch the cornea, an essential part of the eye examination. Methods: AGS and AOA members were surveyed on tonometer preference, tonometer use, disinfection process, disinfectants, disinfection timing, and tonometer damage. Results: Survey responses from 79 AOA members and 197 AGS members are included. The Goldmann tonometer is considered most accurate (70, 89% AOA and 161, 82% AGS). It is preferred by 54 (70%) AOA and 193 (98%) AGS members. Many providers (165) use reusable Goldmann tonometer tips (77, 79% AOA, 88, 45% AGS), and most clean with 70% isopropyl alcohol wipes 59 (77%) AOA and 54 (61%) AGS. In summary, 126 of 276 participants (8, 10% AOA and 118, 60% AGS) follow CDC guidelines by using disposable tips (2 AOA and 109 AGS) or disinfecting reusable tips with 10% hypochlorite (6 AOA and 9 AGS). Conclusions: The majority of AGS providers follow current CDC tonometer disinfection guidelines by shifting to disposable Goldmann tonometer tips. Only a minority of providers who use reusable tonometer tips disinfect with dilute bleach. Continued education on proper tonometer disinfection is critical to prevent eye-care related infection due to improper disinfection. Abstract : Supplemental Digital Content is available in the text.